Restoring Dilapidated Buildings Using Grey Cooperative Games and the fair Distribution of Costs Between the Participating Companies - Emad Qasim; Fathi Emharb; Idris Abdulhamid (AlQalam Journal of Medical and Applied Sciences, 2025)
This paper shows that grey cooperative game theory can help us determine a fair cost between local and international companies to support the problem of restoration, maintenance or even reconstruction of dilapidated housing by using facility location games under uncertainty. Restoration, maintenance, or even reconstruction of dilapidated housing may be a means that must be accomplished before a disaster occurs as pre-emptive planning in order to contribute to better reconstruction and recovery, as well as insuring the lives of residents. In our study, we relied on the old and dilapidated residential quarters in Al-Bayda city. As an example, in our paper, we chose two residential quarter: Red Buildings quarter and White Buildings quarter, as these two quarters are exposed to a disaster that could happen at any moment, God forbid. Some photographs of these dwellings were taken, and they clearly show their deterioration and that they may be on the verge of collapse at any moment (See section 4). Therefore, we will help in restoring and maintaining them through this paper, and two companies will be chosen, one local and the other foreign, for the work for Maintenance and restoration. We will use cooperative grey game theory to help us to restore dilapidated buildings using grey cooperative games and the fair distribution of costs between the participating companies to support this problem using facility location games under uncertainty. توضح هذه الورقة أن نظرية اللعبة التعاونية الرمادية يمكن أن تساعدنا في تحديد التكلفة العادلة بين الشركات المحلية والدولية لدعم مشكلة ترميم أو صيانة أو حتى إعادة بناء المساكن المتداعية باستخدام ألعاب موقع المنشأة في ظل عدم اليقين. قد يكون ترميم أو صيانة أو حتى إعادة بناء المساكن المتداعية وسيلة يجب إنجازها قبل حدوث الكارثة كتخطيط استباقي من أجل المساهمة في إعادة الإعمار والتعافي بشكل أفضل، فضلاً عن تأمين حياة السكان. اعتمدنا في دراستنا على الأحياء السكنية القديمة والمتداعية في مدينة البيضاء. على سبيل المثال، اخترنا في ورقتنا حيين سكنيين: حي المباني الحمراء وحي المباني البيضاء، حيث أن هذين الحيين معرضان لكارثة قد تحدث في أي لحظة، لا قدر الله. وقد تم التقاط بعض الصور لهذه المساكن، وهي تظهر بوضوح تدهورها وأنها قد تكون على وشك الانهيار في أي لحظة (انظر القسم 4). لذلك، سنساعد في ترميمها وصيانتها من خلال هذه الورقة، وسيتم اختيار شركتين، واحدة محلية والأخرى أجنبية، للقيام بأعمال الصيانة والترميم. وسنستخدم نظرية اللعبة التعاونية الرمادية لمساعدتنا في ترميم المباني المتهالكة باستخدام الألعاب التعاونية الرمادية والتوزيع العادل للتكاليف بين الشركات المشاركة لدعم هذه المشكلة باستخدام ألعاب موقع المنشأة في ظل عدم اليقين